AMPLIFIKASI FRAGMEN GEN 18S rRNA PADA DNA METAGENOMIK MADU DENGAN TEKNIK PCR (POLYMERASE CHAIN REACTION) - Prakoso, Satriya Putra; Wirajana, I Nengah; Suarsa, I Wayan (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 7 (2017): Indonesian Journal of Legal and Forensic SciencesDO - 10.24843/IJLFS.2017.v07.i01.p03, 2017)
The aim of this research was to amplificate 18S rRNA gene fragment from honey’s metagenomic DNA using Polymerase Chain Reaction (PCR). The honey sample was collected from Seraya Tengah village, Karangasem regency. The best result of primer design from in silico test was continued to in vitro test using PCR method. The optimum conditions for amplification was obtained as follows: pre-denaturation at 95oC for 3 minutes and continued with 30 of amplification cycle (denaturation at 95°C for 1 minutes, annealing at 55°C for 1 minutes and elongation at 72°C for 1 minutes) and the last step continued with extension process at 72°C for 2 minutes. The size of DNA fragment band of amplified product was about 100 bp which obtained from the honey’s metagenomic DNA.